2016
DOI: 10.1037/fam0000162
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of positive parenting following an acceptance-based couple intervention.

Abstract: Positive parenting practices have been shown to be essential for healthy child development, and yet have also been found to be particularly challenging for parents to enact and maintain. This paper explores an innovative approach for increasing positive parenting by targeting specific positive emotional processes within marital relationships. Couple emotional acceptance is a powerful mechanism that has repeatedly been found to improve romantic relationships, but whether these effects extend to the larger famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
9
0
1
Order By: Relevance
“…The intervention effects on trajectories of the family functioning outcomes over 2 years were not examined because previous research has shown that levels of family functioning behaviors remain relatively stable after initial improvements in family functioning as a result of completing the intervention. 41 Intervention effect sizes were reported by dividing the absolute values of regression coefficients (unstandardized b) by the SD of the residuals of outcomes. 42 In addition, the pooled incidence rate ratio was used as intervention effects for count variables and was calculated by taking the exponent of the regression coefficient (unstandardized b).…”
Section: Discussionmentioning
confidence: 99%
“…The intervention effects on trajectories of the family functioning outcomes over 2 years were not examined because previous research has shown that levels of family functioning behaviors remain relatively stable after initial improvements in family functioning as a result of completing the intervention. 41 Intervention effect sizes were reported by dividing the absolute values of regression coefficients (unstandardized b) by the SD of the residuals of outcomes. 42 In addition, the pooled incidence rate ratio was used as intervention effects for count variables and was calculated by taking the exponent of the regression coefficient (unstandardized b).…”
Section: Discussionmentioning
confidence: 99%
“…A. Cowan et al, 2009;Fagan & Iglesias, 1999;Fagan & Stevenson, 2002;Ferguson & Morley, 2011;Gearing, Colvin, Popova, & Regehr, 2008;Harrison, 1997;Houghton et al, 2015;Landreth & Lobaugh, 1998;Langston, 2016;McCrudden, Braiden, Sloan, McCormack, & Treacy, 2014;Robbers, 2009;Self-Brown et al, 2015;Self-Brown et al, 2017;Siu et al, 2017;Skar, von Tetzchner, Clucas, & Sherr, 2014;Varela, Munoz, Tessier, Plata, & Charpak, 2014;Wilczak & Markstrom, 1999;Wilson, Havighurst, Kehoe, & Harley, 2016) were conducted with fathers only; 10 of the 44 interventions (Caldwell et al, 2014;Caldwell, Rafferty, Reischl, De Loney, & Brooks, 2010;Chacko, Fabiano, Doctoroff, & Fortson, 2018;DeGarmo, Jones, & Rains, 2018;Dilorio, McCarty, & Denzmore, 2006;Ellis, Caldwell, Assari, & De Loney, 2014;Icard, Dilorio, & Fagan, 2012;McBride, 1991;Sandler et al, 2018;Wilson, Havighurst, & Harley, 2014) targeted fathers and their sons; and 11 interventions (Bunston, 2013; C. P. Cowan et al, 2005;P. A. Cowan, Cowan, Pruett, Pruett, & Gillette, 2014;Doherty et al, 2006;McConnell, Barnard, & Taylor, 2017;Morrill, Hawrilenko, & Córdova, 2016;Pruett, Insabella, & Gustafson, 2005;…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Participant sample sizes across studies ranged from 5 to 5,102 participants. Fathers of African descent were the predominant ethnic/ racial group in 16 of the 44 articles (Ashburn et al, 2017;Barth et al, 1988;Block et al, 2014;Caldwell et al, 2014;Caldwell et al, 2010;Dilorio et al, 2006;Ellis et al, 2014;Fagan & Iglesias, 1999;Fagan & Stevenson, 2002;Icard et al, 2012;Rienks et al, 2011;Self-Brown et al, 2015;Self-Brown et al, 2017;Siu et al, 2017;Wilczak & Markstrom, 1999;Wood et al, 2014), followed by 11 studies with predominantly Caucasian fathers (Bunston, 2013;Doherty et al, 2006;Houghton et al, 2015;Landreth & Lobaugh, 1998;McConnell et al, 2017;McCrudden et al, 2014;Morrill et al, 2016;Pruett et al, 2005;Sandler et al, 2018;Wilson et al, 2014;Wilson et al, 2016) and 5 studies with predominantly Hispanic/Latino fathers (Chacko et al, 2018;Concha et al, 2016;P. A. Cowan et al, 2014;P.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…In fact, 55.9% of all households in Japan have nuclear families [1]. e involvement of husbands and partners has been reported to reduce the difficulty of childrearing [11], according to the Basic Survey on Social Life by the Ministry of Internal Affairs and Communications. However, when comparing the childcare time of husbands and wives with children under 6 years old, the time spent raising children was 3.45 hours for wives and only 0.49 hours for husbands [12].…”
Section: Introductionmentioning
confidence: 99%